On an accuracy of the modified UTD solution for a convex impedance cylinder surface - Phaebua, K.; Phongcharoenpanich, C.; Lertwiriyaprapa, T. (My University, 2012)
This paper presents an accuracy of a modified UTD solution for a convex impedance cylinder based on the general 3D UTD solution for a smooth convex perfectly electric conductor (PEC) scattering problem. By employing the impedance boundary condition (IBC), the modified UTD solution for a convex impedance cylinder can be used for the material-coated PEC cylinder problem. Thus, the modified UTD solution for a convex impedance cylinder surface requires the surface impedance value (Z S). In this paper, the study of the limitation of approximated closed form of Z S is presented. The thickness of thin material-coated PEC cylinder will be investigated in terms of the ratio of material-coated thickness to radius of the cylinder. The mean squared error (MSE) between the modified UTD results and the reference results obtained from CST-Microwave Studio program is performed to investigate limitation of closed form of Z S. The relative permittivity ε r of a material-coated PEC cylinder in this paper is fixed to 4. The modified UTD solution result shows good agreement with the CST-Microwave Studio commercial software for the dielectric-coated thickness up to d/a ≤0.07 or d/0.14λ for a=2λ. © 2012 IEEE.
Keywords: Material-coated PEC cylinder; Surface impedance; Uniform Geometrical Theory of Diffraction (UTD)